Surgical and short-term outcomes in robotic and laparoscopic distal gastrectomy for gastric cancer with enhanced recovery after surgery protocol: A propensity score matching analysis - Huang, Weijia; Liu, Siyu; Chen, Junqiang (Frontiers in Surgery, 2022)
Objective This study aims to evaluate the short-term surgical outcomes of laparoscopy-assisted distal gastrectomy (LADG) and robot-assisted distal gastrectomy (RADG) for gastric cancer (GC) with enhanced recovery after surgery (ERAS) protocols. Methods We reviewed the medical records of 202 patients undergoing radical distal gastrectomy; among them, 67 cases were assisted through RADG, while 135 cases were assisted through LADG along with ERAS. We retrospectively collected the medical records in succession from a database (January 2016–March 2019). We adopted propensity score matching to compare surgical and short-term outcomes of both groups. Results After the successful examination of 134 cases, including 67 receiving RADG and 67 undergoing LADG, the operative times were noted as 5.78 ± 0.96 h for the RADG group and 4.47 ± 1.01 h for the LADG group (P < 0.001). The blood loss was noted as 125.52 ± 101.18 ml in the RADG group and 164.93 ± 109.32 ml in the LADG group (P < 0.05). The shorter time to first flatus was 38.82 ± 10.56 h in the RADG group and 42.88 ± 11.25 h in the LADG group (P < 0.05). In contrast, shorter days of postoperative hospital stay were 5.94 ± 1.89 days in the RADG group and 6.64 ± 1.92 days in the LADG group (P < 0.05). Also, the RADG group (84483.03 ± 9487.37) was much more costly than the LADG group (65258.13 ± 8928.33) (P < 0.001). The postoperative overall complication rates, numbers of dissected lymph nodes, visual analogue scale (VAS), and time to start a liquid diet for the RADG group and the LADG group were similar. Conclusions In this research, we concluded that RADG provides surgical benefits and short-term outcomes compared to LADG for GC with ERAS.